Pendampingan terhadap Petani Tembakau dalam Penerapan Akad Muzara’ah di Desa Plalangan, Situbondo - Zainul, Zainul Anwar; Misbah, Misba Huddin (PT Pustaka Cendekia Publisher, 2025)
Plalangan Village is predominantly a tobacco-farming community. In practice, many farmers manage agricultural land through a profit-sharing system using the muzara’ah contract. However, the contract is mostly verbal and undocumented, leading to potential injustices and noncompliance with sharia principles. This community service activity aimed to assist farmers in understanding and implementing muzara’ah contracts properly. The method used was direct mentoring through interviews, observation, and education on Islamic economic principles. The results showed increased farmer understanding of the pillars and conditions of muzara’ah, the importance of written agreements, and the application of fairness and transparency. This assistance encouraged the transformation of muzara’ah practices into more equitable and sharia-compliant arrangements